Slow and Fast Neocortical Oscillations in the Senescence-Accelerated Mouse Model SAMP8 - Castano-Prat, Patricia; Perez-Zabalza, Maria; Perez-Mendez, Lorena; Escorihuela, Rosa M.; Sanchez-Vives, Maria V. (Frontiers in Aging Neuroscience, 2017)
Senescence-accelerated mouse model SAMP8 is characterized by accelerated, progressive cognitive decline as well as Alzheimer disease (AD)-like neurodegenerative changes, and resembles the etiology of multicausal, sporadic late-onset/age-related AD in humans. Our aim was to find whether these AD-like pathological features, together with the cognitive deficits present in the SAMP8 strain, are accompanied by disturbances in cortical network activity with respect to control mice (SAMR1) and, if so, how the alterations in cortical activity progress with age. For this purpose, we characterized the extracellular spontaneous oscillatory activity in different cortical regions of SAMP8 and SAMR1 mice cerebral cortex under ketamine anesthesia at 5 and 7 months of age. Under these conditions, slow oscillations and fast rhythms generated in the cortical network were recorded and different parameters of these oscillations were quantified and compared between SAMP8 and its control, SAMR1 mice. The average frequency of slow oscillations in SAMP8 mice was decreased with respect to the control mice at both studied ages. An elongation of the silent periods or Down states was behind the decreased slow oscillatory frequency while the duration of active or Up states remained stable. SAMP8 mice also presented increased cycle variability and reduced high frequency components during Down states. During Up states, the power peak in the gamma range was displaced towards lower frequencies in all the cortical areas of SAMP8 with respect to control mice suggesting that the spectral profile of SAMP8 animals is shifted towards lower frequencies. This shift is reminiscent to one of the principal hallmarks of EEG abnormalities in patients with Alzheimer’s disease, and adds evidence in support of the suitability of SAMP8 mouse as a model of this disease. Although some of the differences between SAMP8 and control mice where emphasized with age, the evolution of the studied parameters as SAMR1 mice got older indicate that its phenotype tends to converge with that of SAMP8 animals. To our knowledge, this is the first systematic characterization of the cortical slow and fast rhythms in the SAMP8 strain and it provides useful insights about the cellular and synaptic mechanisms underlying the reported alterations.